Tenancy and agricultural land use in Ukraine - Drebot, O.; Voytenko, S.; Kudryk, A.; Kotkova, T.; Lukyanenko, O.; Savchuk, O. (Land Management, Cadastre and Land Monitoring, 2022)
The relevance of the research is due to the needs of planning of agricultural territories and the lack of comprehensive planning and mapping materials both within individual village head districts and on the territory of communities. Also, the conducted research is the basis for the formation of a land bank of specific land owners and land users; obtaining information about the location of land plots, their owner, tenant, area and monetary value. The purpose of the conducted work is visualisation of borders of land shares and study of the comprehensive information on use of share areas. During the research, methods of mapping of territories were used, using analogue and digital mapping materials. Desktop land surveyor software was used to create and process digital data. The limits of all generated cartographic objects have coordinates of turning points, which establishes the work with real spatial objects of the terrain. Research methodology involves a combination of all existing data on land plots, contained in the Ukrainian land cadastre base, as well as non-digital materials to establish the location of land plots, information about which is absent in the cadastre. As a result of research there were formed land plots in vector format within nine village head districts of Radomyshl community, as well as semantic information to each of them. Database, formed as a result of formation of semantic information of each land plot, contains data on the owner, purpose, area, tenant and monetary value. A thematic map of tenants within districts has been created. One of them is presented in the article as an example. The results of the created thematic maps of tenancies within the largest part of the community have been analysed. It was found that 60 % of the land share area has lease agreements. Limited liability companies prevail among the lessees (43 %). A much smaller area is rented by private enterprises (15 %) and farms (9 %). Not a single land parcel (share) is used by the owner. Despite the large rental area, the number of tenants is not significant. In total, there are 18 limited liability companies, 4 private enterprises and 9 farms. There are also private leases by citizens who are not owners of shares. The research presents data on the agricultural development of the study area and monetary value of the land shares. It was found that the actual ploughing is over 90 %, which is a significant indicator compared to other communities of Zhytomyr. Moreover, the area of reserve lands constitutes almost 1 thousand ha, which is 3 % of the total surveyed area. The largest area of reserve lands within the district is about 300 ha. On average, this figure is close to 100 ha. There are exceptions, districts, where there are no reserve lands at all. Within the study area, there is one district without reserve lands and one district with a comparatively small area (36 ha). The monetary value of land is low. The lowest monetary value of 1 hectare is 85 EUR, the highest - approximately 700 EUR. The average monetary value of the land is in the range of 300 EUR. The results obtained constitute a potential platform for the formation of fields; exchange of land plots to avoid "checkerwork" in the land use process; entering into lease agreements for the shares that are not legally used; arranging territories, which data are not available in the cadastre.In addition, the studies carried out are an integral part of community-wide surveys. There are also plans to extend them to a larger area to draw conclusions about the tenancy system within the Polissia region of Zhytomyr Oblast.Keywords: lease relations, land management, lease of shares, agricultural land, land fund, territorial community.
Keywords: land management; lease of shares; agricultural land